Doubtful Food, Doubtful Faith: A Comparative Study of the Influence of Religious Maximalism on New Ideas of Food Taboo in Some Contemporary Jewish and Muslim Communities - Theobald, Simon (International journal for the study of new religions, 2012)
The encroachment of maximalist thinking in Jewish and Muslim communities globally has been widely noted by scholars across disciplines. Todate, the influence of such thinking on the cultural construction of foodways, particularly food taboos, within these communities has been largely ignored. This article seeks to address shortcomings in this area of research. Using both fieldwork data from communities in Sydney, Australia, and digital ethnography, this article problematizes anthropological material that suggests that kosher and halal necessarily unite diverse co-religionists. Today, fundamentalists within these faith groups use the concept of "stringency" or "exactingness" in association with food preparation and products to reinterpret the concept of taboo. This process undermines normative communal ideation pertaining to food, providing fundamentalists opportunity to reject intra-communal commensality. Taboos then cease to function as a symbolic marker of communal unity, instead serving the anti-pluralist agenda of fundamentalists. In this way, food becomes the symbolic medium through which the discourse of communal legitimacy, authenticity, and purity, is paradoxically both achieved and rejected.